2022
DOI: 10.1097/adm.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BEAT Meth Intervention for Emergency Department Patients with Methamphetamine Psychosis

Abstract: ObjectivesMethamphetamine is the second leading cause of overdose death in America and a leading cause of emergency department (ED) visits. Methamphetamine-induced psychosis is a dangerous and difficult-to-treat consequence of methamphetamine use. We describe the pilot implementation and outcomes of a multimodal treatment intervention for ED patients with methamphetamine psychosis, Beginning Early and Assertive Treatment for Methamphetamine Psychosis (BEAT Meth).MethodsBEAT Meth was implemented in an urban saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…50 At an urban safety net hospital, patients enrolled in an intervention, including early identification and treatment of methamphetamine psychosis, protocolized hospitalization, and linkage to outpatient treatment were more likely to attend an outpatient specialty addiction appointment. 51 Importantly, we found that providers frequently “ignored” stimulant use or did not differentiate between specific SUDs when patients used multiple substances. Stimulant-specific order sets may help standardize treatment and encourage hospital providers to address stimulant use by providing them with a protocolized treatment option.…”
Section: Discussionmentioning
confidence: 77%
“…50 At an urban safety net hospital, patients enrolled in an intervention, including early identification and treatment of methamphetamine psychosis, protocolized hospitalization, and linkage to outpatient treatment were more likely to attend an outpatient specialty addiction appointment. 51 Importantly, we found that providers frequently “ignored” stimulant use or did not differentiate between specific SUDs when patients used multiple substances. Stimulant-specific order sets may help standardize treatment and encourage hospital providers to address stimulant use by providing them with a protocolized treatment option.…”
Section: Discussionmentioning
confidence: 77%
“…Hospitals may need to provide additional supports the address the comorbidities and referral process to outpatient treatment to improve patient outcomes for this unique population. For example, one safety-net hospital implemented an early identification, medication, and behavioral management protocol for methamphetamine use which was associated with increased outpatient addiction treatment attendance ( Simpson et al, 2023 ). Additionally, the high proportion of methamphetamine- and co-use-involved stays which were paid for by Medicaid highlights the importance of Substance Use and Mental Health Block Grants and 1115 Waivers for developing and testing treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalizations indicating methamphetamine or co-use had a high proportion of schizophrenia and psychosis. It is important that care teams are able to differentiate between, and appropriately treat, methamphetamine-induced psychosis and other psychiatric conditions ( Priest et al, 2023 ; Simpson et al, 2023 ). Additionally, we found a high proportion of methamphetamine- and co-use related stays also indicated PTSD or.…”
Section: Discussionmentioning
confidence: 99%
“…9 Methamphetamine is a leading cause of substancerelated ED visits. 10,11 The reasons for seeking ED care when using methamphetamine varies with patients requiring anything from medical evaluation for chest pain to sedation and psychiatric evaluation for agitation and psychosis. 12 In some areas, behavioral crises related to methamphetamine use account for half of psychiatric emergency services visits.…”
Section: Introductionmentioning
confidence: 99%